Mexican native fauna at risk and the NOM-059 listing. Are all the called there, and are those there called? - García-Aguilar, María C.; Luévano-Esparza, Jaime; De la Cueva, Horacio (Instituto de Ecología, A.C., 2017)
The Norma Oficial Mexicana 059 (NOM-059) is the Mexican legal instrument that identifies species or populations at risk throug the use of the Método de Evaluación de Riesgo de Extinción de Especies Silvestres de México (MER). From its first promulgation in 1994, the NOM-059 has been used as a reference to assess the conservation status, and as a tool on national environmental policies; however, it has been questioned for the lack of scientific criteria. We assess the relevance of the NOM-059 as a tool to assess the conservation status of Mexican native species by utilizing the mammals as a case study. More than 40% of native mammals are included in the list, though only 10% of the listed species had been evaluated with the MER, and have technical support to justify their inclusion. In most cases, criteria used to determine the species inclusion are unknown, in the other cases the criteria are contradictory with the objectives and methods stablished in the NOM-059. Non-endemic mammals are overrepresented in the list, while the extinction risk of the endemic mammals is underestimated.The evidence shows that in its current form the NOM-059 it is not an adequate tool to assess the species conservation status. Finally, we list a series of recommendations that would improve NOM-059 and strengthen conservation efforts in Mexico.